miR-127-5p regulates FAIM2-mediated cell apoptosis and participates in cerebral ischemia-reperfusion injury: miR-127-5p regulates FAIM2 in CI/RI - Hu, Teng; Lin, Yongzhong (Cellular and Molecular Biology, 2024)
Mechanical thrombectomy (MT) has become an effective re-airway method for cerebral ischemia-reperfusion injury (CI/RI). However, at present, there are few studies on the impact of MT therapy on the prognosis of CI/RI patients at home and abroad. Therefore, this paper aims to analyze the relevant factors affecting the prognosis of CI/RI patients after MT therapy. The main regulatory miRNAs during CI/RI in patients with MT were screened and studied. Serums were obtained from 80 patients (moderate to severe stroke) who underwent MT. Clinical information was recorded using a unified standard questionnaire. According to the modified Rankin Scale, the patients were divided into a good prognosis group and a poor prognosis group. The clinical data were compared respectively, and univariate and multivariate Logistic regression analysis was performed. ROC curves were drawn, and Kaplan-Merier method determined whether different NIHSS scores at admission had any difference in the in-hospital survival rate of CI/RI patients treated with MT. miRNAs in serum were detected and screened out. Cell and animal models were established, in which miRNAs and apoptotic molecules were detected. miRNA target genes were predicted, and the mechanism of miRNA regulation of apoptosis was verified. Gender, smoking, drinking, diabetes, hypertension, hyperlipidemia, age, and alcohol consumption suggested no difference in the two groups. The rates of smoking history, diabetes, hypertension, and hyperlipidemia in the poor prognosis group were higher than those in the good prognosis group. Smoking and diabetes were independent risk factors for poor prognosis. miR-127-5p expression in CI/RI patients with poor prognosis was higher than that in those with good prognosis. miR-127-5p expression was also elevated in both cell and animal models. Cell apoptosis was weakened after miR-127-5p knockdown, and tissue infarction in animal models was also reduced. FAIM2 was a target gene of miR-127-5p. silencing FAIM2 enhanced apoptosis after miR-127-5p knockdown. miR-127-5p/FAIM2 axis can be a new strategy to treat and prevent brain injury in CI/RI patients treated with MT.